An Analysis of Grice's Maxims in Finding Nemo and Finding Dory Movies - Anak Agung Megantari Putri; I Gusti Agung Istri Aryani; I Nyoman Arya Wibawa (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study explores the application and violation of Grice's conversational maxims in the animated films "Finding Nemo" (2003) and "Finding Dory" (2016). Grice's maximsquantity, quality, relation, and manner are key to effective communication in pragmatics. The research analyzes how these maxims are followed or flouted by the characters, affecting humor, tension, and narrative flow. Through a qualitative approach, the study identifies specific instances of adherence and violation, examining their impact on character development and audience engagement. The findings indicate that flouting the maxim of quantity often creates humor, while manipulating the maxim of relation generates suspense. This analysis demonstrates the role of conversational maxims in enhancing storytelling and character interactions in animated films, contributing to their narrative and entertainment value.